Endothelium modifications in the climacteric woman - Romero Galván, Edgardo (2018)
The endothelium is the largest vascular endocrine organ protected in women by estrogens and mediated through nitric oxide, a potent vasodilator. The woman is protected from atherothrombosis until the menopause. At the beginning of the climacteric this protection is lost and endothelial dysfunction leads to cardiac and brain vascular risk factors such as hypertension, diabetes and dyslipidemia, which increase the vascular damage and the risk of heart attack.